Video Library of Mathematics Lessons as a Means of Methodological Training for Future Primary School Teachers - Skvortsova Svіtlana; Haran, Maryna; Sagan, Olena (International Journal of Research in E-learning, 2020)
The authors substantiate the expediency of using video lessons and their fragments in the process of forming future teachers’ professional competency. The elaborated library includes video recordings of real mathematics lessons at primary school and videos of pupils solving certain types of problems with full commentaries, structured by classes and topics. The methods of using the video library by educators in the field Methods of Teaching Mathematics in Primary School and students majoring in specialty 013 Primary Education were developed. The effectiveness of using the video library as a means of teaching the course Methods of Teaching Mathematics in Primary School was verified experimentally by introducing it into the educational process of three Ukrainian universities.